The Effect of Ice Floe on the Strength, Stability, and Fatigue of Hybrid Flexible Risers in the Arctic Sea - Dimitrii Korotygin; Sathish. K. Nammi; Ketan Pancholi (Journal of Composites Science, 2023)
Flexible risers have proven to be a popular choice for deepwater exploration due to their ability to withstand functional and environmental stress while maintaining system integrity. In the challenging arctic conditions, lightweight hybrid composite flexible risers are likely to be employed to mitigate the increase in effective tension. This study investigates the strength and stability performance of production hybrid composite flexible risers with composite pressure armour in the harsh environmental conditions of the Arctic seas. At a water depth of 340 m, the flexible riser was analysed in various global configurations to evaluate the static, dynamic, and lamina-scale performance of its carbon fibre-reinforced thermoplastic polymer composite layer. The drifting ice in the region generated additional load on the riser system, and the effects of this ice on the riser design and its dynamic and lamina-level performances were also analysed. The results indicate that the current riser design incorporating the composite layer is insufficient to ensure system integrity without mitigating the effects of ice loading. The carbon fibre direction in each lamina must be optimised for excess axial stress emanating from the combined action of hoop, axial, and bending stresses. Finally, recommendations on how to improve the life of the lightweight hybrid composite riser in arctic conditions are provided.